Winter supplemental feeding of dairy heifers maintained in "colonião" grass pastures - Lima, Carlos Rodrigues; Aronovich, Salomão; Souto, Sebastião Manhães (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was conducted during the winters of 1968 and 1969 to study the effect of roughage supplementation during the dry period (140 days) on the weight gain of Holstein x Zebu crossbred heifers being maintained in "colonião" (Pannicum maximum Jacq.) grass pastures. The supplemental roughages used were sorghum silage (Sorghum vulgare Pers.), chopped elephant grass (Pennisetum purpureum Schum.) and chopped sugar cane (Saccharum officinarum L.). Each of the supplemental roughages was fed at the rate of 10 kg per head per day. Average daily gains were 164 gm for the heifers maintained in pasture without supplementation (controls) and 314, 277 and 261 gm, respectively, for those supplemented with sorghum silage, elephant grass and sugar cane. During 1968, the drier of the two years, there was an evident superiority for sorghum silage and a reduced effect for elephant grass. In general, the cost of supplemental feeding showed a direct relationship with the average daily gain obtained. However, elephant grass produced the cheapest gain and sugar cane the most expensive. Even though a positive response was obtained from supplemental feeding which would permit calving at a younger age, it is considered necessary that other experiments be conducted to determine the best and cheapest way to feed heifers destined for the dairy herd.